Complete Caudate Lobectomy: Its Definition, Indications, and Surgical Approaches. Issue 2 (1998) - Sasada, Akinori; Ataka, Keiji; Tsuchiya, Kazuhiko; Yamagishi, Hiroyuki; Maeda, Hiromi; Okada, Masayoshi
Abstract : There are three ways to approach and resect the caudate lobe of the liver, that is; and isolated caudate lobectomy, a combined resection of the liver overlying the caudate lobe, and a transhepatic anterior approach by splitting parenchyma of the liver. We had two patients with neoplasms originating in the caudate lobe who underwent a complete caudate lobectomy. Both patients have been doing well without liver dysfunction. Although after the transhepatic anterior approach we anticipated an adverse effect from splitting the parenchyma of the liver, the postoperative course was uneventful and similar to that of the right side approach.